2018
DOI: 10.1149/2.0041809jes
|View full text |Cite
|
Sign up to set email alerts
|

Designing Polyolefin Separators to Minimize the Impact of Local Compressive Stresses on Lithium Ion Battery Performance

Abstract: In this paper, we study how polyolefin separators respond to compressive stress, which can occur during battery operation as active particles lithiate, expand, and push into and deform the separator. We use real microstructures of polyethylene and polypropylene separators acquired with focused ion beam scanning electron microscopic (FIB-SEM) tomography and simulate how these structures deform under compressive strain. After validating our mechanical simulations, we characterize how the microstructural properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 42 publications
2
58
1
Order By: Relevance
“…Lagadec et al [ 36 ] characterized how the microstructural properties (including porosity, tortuosity, and permeability) of the separators change as a function of compressive strain and predicted the influence of these changes on the Li-ion transport through the separator by mechanical simulations. They also concluded that a given compressive strain negatively impacts the microstructure of PE separator more than that of a PP separator, because PE has a lower Young’s modulus, smaller pore sizes, and a more isotropic structure.…”
Section: Numerical Study Of Separatorsmentioning
confidence: 99%
“…Lagadec et al [ 36 ] characterized how the microstructural properties (including porosity, tortuosity, and permeability) of the separators change as a function of compressive strain and predicted the influence of these changes on the Li-ion transport through the separator by mechanical simulations. They also concluded that a given compressive strain negatively impacts the microstructure of PE separator more than that of a PP separator, because PE has a lower Young’s modulus, smaller pore sizes, and a more isotropic structure.…”
Section: Numerical Study Of Separatorsmentioning
confidence: 99%
“…The separator is placed between two electrodes to prevent direct contact between them while serving as the electrolyte reservoir to enable ionic transport 6–11 . Many researchers have found that the pore structure of battery separators affects battery performance 12–18 . Even separators with the same porosity and through‐plane tortuosity exhibit different performances 19,20 …”
Section: Introductionmentioning
confidence: 99%
“…So far, it is still a great challenge to establish an accurate model between mechanical properties of local components and the capacity because of the diversity and complexity of materials. For example, the pressure on the separator changes with the aging of the battery [18]. The porous size of the electrode, the pressure in the manufacturing process, and the electrolyte around it also affect its mechanical properties [19].…”
Section: Introductionmentioning
confidence: 99%